Tinjauan kesiapan penyusunan laporan keuangan sesuai SAK EMKM pada UMKM di Banyuwangi - Kareja, Novilia; Alfiyah, Nurul; Wicaksono, Dani Agung (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The research aims to obtain an overview of the readiness of MSMEs in Banyuwangi in preparing financial reports according to SAK EMKM. This review of MSME readiness is carried out on several aspects, namely the ability to fulfill characteristics, the level of ability to fulfill basic assumptions and the basis for measurement. Descriptive research with a qualitative approach is a form of this research. Respondents in this study were tenants assisted by the Banyuwangi State Polytechnic Business Incubator. The results of this study show that from the level of ability to fulfill the basic assumptions it is known that the level of ability is still very minimal. Of the three basic assumptions for preparing financial reports according to SAK EMKM, only the basic assumptions of business continuity can be fulfilled by all respondents. Meanwhile, the accrual basis and business entities are still not optimally applied by some SMEs.